Rintihan - Kamilia Maghfudzah; Herlinda Mansyur (SENDRATASIK UNP, 2020)
The "Moans (Rintihan)" artwork aims to elevate personal life into motion elements, create dance artworks, stimulate art performers to increase creativity in art and express the experience of writers as beginner choreographers in the field of dance art creation. The form of presentation in the “Moans (Rintihan)" artwork was representational. The “Moans (Rintihan)" artwork depict family activities that began with a beauty and harmony of the family that end in something not as expected. In this work, the choreographers used movements that have meaning and pure motion that had been distributed with motion techniques adapted to the theme, so that the designs of motion have strenght that could be used as starting points in the work, the most preferred in this work was aesthetic of the motions, full of soul and artistic motions, since the dance is also the choreographer’s priority.